2016
DOI: 10.3390/jmse4020031
|View full text |Cite
|
Sign up to set email alerts
|

On the Sediment Dynamics in a Tidally Energetic Channel: The Inner Sound, Northern Scotland

Abstract: Sediment banks within a fast-flowing tidal channel, the Inner Sound in the Pentland Firth, were mapped using multi-frequency side-scan sonar. This novel technique provides a new tool for seabed sediment and benthic habitat mapping. The sonar data are supplemented by sediment grab and ROV videos. The combined data provide detailed maps of persistent sand and shell banks present in the Sound despite the high energy environment. Acoustic Doppler Current Profiler (ADCP) data and numerical model predictions were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…The tidal current velocities and the bed shear stress fields calculated by McIlvenny et al [11] using a 2D hydrodynamic model were largely consistent with the observed sediment distributions, with sediment banks lying adjacent to the main flow through the Inner Sound. However, as with [8], the depth-averaged modelled velocities used by McIlvenny et al [11] cannot be considered ideal to calculate bed shear stress fields.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…The tidal current velocities and the bed shear stress fields calculated by McIlvenny et al [11] using a 2D hydrodynamic model were largely consistent with the observed sediment distributions, with sediment banks lying adjacent to the main flow through the Inner Sound. However, as with [8], the depth-averaged modelled velocities used by McIlvenny et al [11] cannot be considered ideal to calculate bed shear stress fields.…”
Section: Introductionsupporting
confidence: 79%
“…Bed shear stress is a key parameter in the erosion of seabed sediment, and understanding potential implications of tidal energy developments on local sediment dynamics requires first an estimate of possible changes to the bed shear stress. Building on the 2D modelling work reported by McIlvenny et al [11], we extend the modelling study to three dimensions, thereby resolving the vertical structure of the flow; we expect this to improve the estimates of near-bed velocity and therefore local bed shear stress during flood and ebb tides, and to allow better predictions of the potential changes to bed shear stress following the installation of tidal turbines in the region. In the following sections, we briefly describe the formulation of the model, including the parameterization of tidal turbines, and verify its performance against observations of sea surface height (SSH) and tidal current velocity.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations